2020
DOI: 10.3390/ijms21144908
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in Liver Diseases: An Overview

Abstract: Ferroptosis is an iron-dependent form of cell death characterized by intracellular lipid peroxide accumulation and redox imbalance. Ferroptosis shows specific biological and morphological features when compared to the other cell death patterns. The loss of lipid peroxide repair activity by glutathione peroxidase 4 (GPX4), the presence of redox-active iron and the oxidation of polyunsaturated fatty acid (PUFA)-containing phospholipids are considered as distinct fingerprints of ferroptosis. Several pathways, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
169
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 233 publications
(187 citation statements)
references
References 76 publications
0
169
0
Order By: Relevance
“…Meanwhile, O 2can bind hydrogen ions to produce H 2 O 2 . (Capelletti et al, 2020). This process prevents the formation and accumulation of iron-dependent lipid ROS.…”
Section: Gpx4 and Ferroptosismentioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, O 2can bind hydrogen ions to produce H 2 O 2 . (Capelletti et al, 2020). This process prevents the formation and accumulation of iron-dependent lipid ROS.…”
Section: Gpx4 and Ferroptosismentioning
confidence: 99%
“…During ferroptosis, ROS are produced from the Fenton reaction, which is a process of producing hydroxide (OH − ) and hydroxyl (OH • ) by the reaction between Fe 2+ and H 2 O 2 (Mittler, 2017). Moreover, The Haber-Weiss cycle showed that Fe 3+ is reduced to Fe 2+ through the reaction with superoxide (O 2− ), and Fe 2+ reacts with H 2 O 2 to form OH • , OH − , and Fe 3+ (Capelletti et al, 2020). Thus, Fe 2+ is conducive to the production of ROS and promotes lipid peroxidation, thus inducing ferroptosis.…”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%
See 3 more Smart Citations